Diferenciais salariais e mercado potencial: evidências para o Brasil - Pedro Vasconcelos Maia do Amaral (2008)
Brazil presented in the last 30 years not only periods of economic growth but also crises and stagnation. The Brazilian regions performance (in face of the challenges and opportunities presented during this period) was not even at all, as we can see by the massive regional imbalances around the country. To understand the factors that influence the production (in total or per capital levels) is crucial to wealthy improvements and reduction of disparities. What are its determinants is a controversy question. The theoretical approaches identify different factors as related to economic growth. The purpose of this essay is to analyze the unbalances on the regional production under the light of the New Economic Geography. As usual in the literature, one way to perform this empirical verification is thru the NEGs wage equation.Using 1980, 1991 and 2000 Brazilian Census data (at comparables municipalities areas), this essay aims to estimate the NEG wage equation, using panel data model with spatially correlated errors components. The results point to a strong relationship between market potential and wages, indicating that the NEG theoretical framework might be well fit to recent Brazilian municipalities reality.